2009
DOI: 10.1177/097185241001300305
|View full text |Cite
|
Sign up to set email alerts
|

Women in Higher Education: A Concern for Development?

Abstract: Women's education is currently at the center of international development discourse. In the discourse on education and development, "education" has tended to mean primary-and to an extent, secondary-education. The issue of higher education has so far received modest attention. This article examines the global situation of women, higher education, and development; suggests some possible reasons for the modest academic as well as policyrelated debate on the issue; and considers some implications of the situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Additionally, Buckner (2013) found that in Egypt, gender is an important predictor of university enrollment and that women are much more likely to be enrolled in humanities, arts, and education, rather than in fields like engineering. Similarly, Tjomsland (2009) noted gender segregation in the Arab‐Muslim world and that the proportion of women in higher education has historically been very low in most Arab countries. That said, some countries, such as Egypt and Tunisia, now offer free higher education, which could help to increase enrollment and could be one step toward increasing equality among men and women (Krafft & Alawode, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, Buckner (2013) found that in Egypt, gender is an important predictor of university enrollment and that women are much more likely to be enrolled in humanities, arts, and education, rather than in fields like engineering. Similarly, Tjomsland (2009) noted gender segregation in the Arab‐Muslim world and that the proportion of women in higher education has historically been very low in most Arab countries. That said, some countries, such as Egypt and Tunisia, now offer free higher education, which could help to increase enrollment and could be one step toward increasing equality among men and women (Krafft & Alawode, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Among those profiles with more women, women typically performed highest on GRE Verbal and lowest on GRE Quantitative, which is expected based on trends in test scores from the past 5 years (ETS, 2019a). Even though women are highly represented in graduate education, cultural values and expectations still play a role in access to higher education for women (Tjomsland, 2009). Additionally, STEM‐based fields tend to be the most sought‐after fields for international students and to be dominated by men, which could be another reason for the lower proportion of women in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien las mujeres que ingresan a la educación superior en la adultez exhiben un alto compromiso, reportan un incremento en su confianza e independencia personal y, a la vez, consideran entregar un ejemplo a sus hijos (O'Shea & Stone, 2011), simultáneamente enfrentan el desafío de combinar sus estudios con responsabilidades familiares y trabajo doméstico y remunerado. En este sentido, la retención en programas vespertinos indica que el abandono por parte de estudiantes femeninas es más alto (Kimoga et al, 2015), considerando además su situación de menores ingresos o dependencia económica (Kimoga et al, 2015;O'Shea & Stone, 2011;Tjomsland, 2009;Wang et al, 2016). Con todo, las estudiantes vespertinas perciben poco apoyo institucional focalizado, como becas o ayudas económicas a madres solteras, falta de seguridad en los campus durante la noche, falta de orientación para enfrentar su sobrecarga académica, personal y/o laboral (Ibíd.…”
Section: Las Experiencias Universitarias Vespertinasunclassified
“…Further the transformative possibilities of feminisms in engineering education (Riley, Pawley, Tucker, & Catalano, 2009) is finding more women and diversity in engineering fields (Hopewell, McNeely, Kuiler, & Hahm, 2009) that could transform women in non-traditional sectors of the economy with less gender segregation in workplace (Potter & Hill, 2009). It's a teaser to worry about women in science (Rosser & Taylor, 2009) though the larger concern would be women stand out as a highly efficient way of shaping more gender-equitable situation in higher education (Tjomsland, 2009) Understanding women's underrepresentation in engineering (Morganson, Jones, & Major, 2010) states back to identifying low representation of women in engineering with fewer opportunities than male peers and acutely feel the lack of role models, in work domain and indirect roles (A. E. Smith & Dengiz, 2010). Education, hence by far is gender shaped (Apple, 2010) with feminism in engineering being just more than a girls talk (Larkin & Quinn, 2010).…”
mentioning
confidence: 99%